2013
DOI: 10.1093/jscr/rjs033
|View full text |Cite
|
Sign up to set email alerts
|

A presentation of facial necrotizing fasciitis with orbital involvement

Abstract: Necrotizing fasciitis is a rare, severe, life-threatening soft tissue infection. Rapid progression and systemic illness are recognized features of the condition in which a high index of suspicion is essential to prompt early diagnosis and ensure a favourable outcome. Management necessitates immediate and aggressive surgical and antimicrobial treatment. This case report describes the rare presentation of facial necrotizing fasciitis with orbital involvement that required initial and subsequent widespread surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Blood investigations (often characterised by a markedly elevated white cell count), microbiological and histopathological analysis will aid diagnosis, but NSTI is a clinical diagnosis and should be acted upon immediately. [1][2][3][4] A diagnostic tool for distinguishing NSTI from other soft tissue infections was developed by Wong et al 7 in 2004: the laboratory risk indicator for necrotising fasciitis (LRINEC) score (Table 1). This tool includes six parameters and has a reported positive predictive value of 92.0% and negative predictive value of 96.0%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood investigations (often characterised by a markedly elevated white cell count), microbiological and histopathological analysis will aid diagnosis, but NSTI is a clinical diagnosis and should be acted upon immediately. [1][2][3][4] A diagnostic tool for distinguishing NSTI from other soft tissue infections was developed by Wong et al 7 in 2004: the laboratory risk indicator for necrotising fasciitis (LRINEC) score (Table 1). This tool includes six parameters and has a reported positive predictive value of 92.0% and negative predictive value of 96.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of initial surgical intervention is the most important prognostic determinant in NSTI. [1][2][3][4][5][6][7][8][9] Nisbet et al 11 reported in a case series of 82 adult patients that a 43% mortality rate existed when surgical input was greater than 24 h from recognition of infection; when surgery occurred within 24 h, this figure decreases to 16%. Early identification is clearly crucial in management of NSTI; however, it has been shown that NSTI is correctly diagnosed prior to admission to hospital only 14% of the time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periorbital necrotizing fasciitis is a progressive, rapidly spreading and destructive polymicrobial infection involving the skin, subcutaneous and deep soft tissue 1 . It is commonly associated with traumatic events in patients with compromised immune systems, diabetes, chronic steroid use and alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Necrotizing fasciitis is a potentially fatal, rapidly progressive soft tissue infection that involves fascial planes, initially sparing overlying skin and underlying muscle. [ 1 2 3 4 5 6 ] Necrotizing fasciitis has been referred to by many different names such as hospital gangrene, flesh eating disease, streptococcal hemolytic gangrene, synergistic necrotizing cellulitis, and Fournier's gangrene when it involved the perineum. [ 1 3 7 8 ] It was described by Joseph Jones in 1871 during the American Civil war but was first described as necrotizing fasciitis in 1952 by B.…”
Section: Introductionmentioning
confidence: 99%